Trends in the Epidemiological Distribution of ARI Cases in Toddlers in Kendari City in 2021-2023 - Amay, Almaghfirah Ferisya; Tosepu, Ramadhan (Universitas Mandala Waluya, 2024)
Acute Respiratory Infections (ARI) cause an estimated 4 million deaths each year, with infants, children and the elderly being the groups most at risk. Every year, more than 2 million children under five years of age die from ARI. This study aims to describe trends in the incidence of ARI in children under five years of age in Kendari City from 2021-2023. This type of research is descriptive, with an observational research design. The population and sample of this study were all toddlers who suffered from ARI in Kendari City in 2021-2023, totalling 23,508 toddlers (total sampling). The results showed that the number of ARI cases in toddlers in Kendari City increased yearly. In 2021, the prevalence was 24%; in 2022, it increased to 36.2%; in 2023, it reached 39.7%. During 2021-2023, the number of ARI cases among male toddlers (52.7%) was higher than among female toddlers (47.2%). Based on age group, 25.2% of cases occurred in toddlers aged <1 year, while 74.7% occurred in toddlers aged 1-<5. The health centre with the highest number of ARI patients is Puskesmas Puwatu, with a case contribution of 15.5%, while Puskesmas Jatiraya has the lowest number of cases, which is 0.9%. This study concludes an increasing trend in children under five with ARI in Kendari City from 2021-2023. Therefore, it is recommended that the health centres educate through posyandu activities about the dangers of ARI in toddlers and effective prevention and control efforts.